2017
DOI: 10.3390/nu9091015
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation and Non-Alcoholic Fatty Liver Disease: Present and Future

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic hepatic disease throughout the Western world and is recognized as the main cause of cryptogenic cirrhosis; however, the identification of an effective therapy for NAFLD is still a major challenge. Vitamin D deficiency is a wide-spread condition which reaches epidemic proportions in industrialized countries, mainly in relation to current lifestyle and limited dietary sources. Epidemiological studies point towards an association between hypovit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…Several observational studies reported a link between low 25(OH)D plasma levels and fatty liver diseases [13,[47][48][49]. If the causality is still not clearly demonstrated in humans [50], observations on animal models, including the present study, tend to confirm such an assumption.…”
Section: Discussionsupporting
confidence: 56%
“…Several observational studies reported a link between low 25(OH)D plasma levels and fatty liver diseases [13,[47][48][49]. If the causality is still not clearly demonstrated in humans [50], observations on animal models, including the present study, tend to confirm such an assumption.…”
Section: Discussionsupporting
confidence: 56%
“…9, 10-Secoergosta-7, 10 (19), 22-triene-3, 5, 6-triol is one form of dehydrocalciferol from vitamin D 31 . Hydroxyvitamin D form in the body will affect the health of a human's liver 32 .…”
Section: Gracilismentioning
confidence: 99%
“…Vitamin D knockout mice spontaneously developed liver fibrosis, while mice fed a vitamin D‐deficient diet developed severe hepatic steatosis and inflammation,82, 83 demonstrating that NAFLD may be associated with vitamin D deficiency. However, clinical studies on vitamin D supplementation on NAFLD pathogenesis have been limited; thus, more studies are needed to provide conclusive results 84. On the other hand, studies have shown that PXR can activate de novo lipogenesis in an SREPB1c‐dependent manner.…”
Section: Nuclear Receptors As Therapeutic Targetsmentioning
confidence: 99%